THE ENHANCEMENT OF COGNITIVE ABILITIES IN EARLY CHILDHOOD THROUGH PICTURE CARD GAME - Marliana, Ratna Lina; Hendriana, Heris; Afrilianto, Muhammad (Jurnal Empowerment, 2024)
The purpose of this study is to analyse the students’ cognitive ability in the terms of reasoning which are relation to numbers and orders, and the application of learning that has not developed yet as what the teachers hope. This research is aimed to see how the early childhood can develop their cognitive ability by using picture card game. The type of this research is classroom action research (CAR) that has been done in three cycles. The subject of this research is early childhood as many as 16 students consisting of 8 male students and also 8 female students that age 4 to 5 years old. The researcher used observation, interview, and questionnaires as the instruments for data collection techniques. Then, the researcher analysed the data using qualitative method and it was also completed with quantitative analysis called as descriptive statistical analysis through percentage count. The finding of this research is there is a significant development of children’s cognitive ability in the terms of reasoning and numeracy ability. The development of early childhood skill in every cycle becomes an indicator where the result of pre-cycle to the children in development stage is 31, 25%. In the first cycle, it developed into 37, 5%, the second cycle increased into 43, 75%, and for the third cycle it became 56, 25%. The result of those all activities are that the application of picture card game can develop cognitive ability to early childhood. The use of picture card media will be much better if it is implemented with a various variety of game.